PENGELOLAAN KELAS UNTUK ANAK DIDIK TINGKAT DASAR - Ismah (EL ROBIH: Jurnal Pendidikan Madrasah Ibtidaiyah, 2025)
This study aims to examine the strategies and effectiveness of classroom management in supporting the teaching and learning process at the elementary level. Proper classroom management is believed to create a conducive learning environment, enhance student engagement, and support their cognitive and social development. The research employs a qualitative approach using observation, interviews, and documentation techniques conducted in several elementary schools. The findings indicate that classroom layout, lighting, ventilation, cleanliness, and the arrangement of learning materials significantly affect students' concentration and learning comfort. Furthermore, teacher involvement in organizing and maintaining the classroom plays a crucial role in the success of classroom management. The study recommends the need for teacher training in classroom management and institutional support to create more child-friendly learning spaces.